How well does color perimetry isolate responses from individual cone mechanisms? - Simunovic, M; Cullerne, A; Colley, A; Wilson, T (2004)
PURPOSE: Over the past two decades there has been renewed interest in the use of color perimetry as a means of detecting early functional defects resulting from glaucomatous optic neuropathy and other forms of ophthalmic and neurologic pathology. The most popular form of color perimetry employs a colored background that selectively desensitizes two of the cone mechanisms, while the wavelength of the test target is selected to favor detection by the remaining, relatively unadapted, cone mechanism. While there are data to support the assertion that blue on yellow perimetry adequately isolates the short wavelength sensitive (SWS) cone mechanism, the only estimates of isolation of the other two cone mechanisms are for the region of the visual field corresponding to the fovea. The purpose of this experiment was thus to determine the amount of cone mechanism isolation that is afforded by automated perimetry when using yellow, blue, and magenta adapting backgrounds. METHODS: To estimate cone mechanism isolation, we determined spectral sensitivity for a range of narrow-band stimuli using a standard 30-2 program on a modified Humphrey perimeter. Targets were presented against three different backgrounds of different luminance; yellow at 2.1 log cd.m-2, magenta at 1.3 log cd.m-2, and blue at 1 log cd.m-2. Sensitivity values for each background at each stimulus position were plotted as a function of wavelength, normalized, and then fitted with cone sensitivity templates to determine the relative sensitivity of the three cone mechanisms. RESULTS: The maximum relative isolation of an individual cone mechanism was achieved with a yellow background, where there was an average relative isolation of 0.94 for the SWS cone mechanism; the blue background provided a relative isolation of 0.89 for the long wavelength sensitive (LWS) cone mechanism. The magenta background proved poor at isolating the medium wavelength sensitive (MWS) cone mechanism, where a relative isolation of only 0.51 was obtained. CONCLUSION: Although color perimetry is capable of isolating individual cone mechanisms, the magnitude of isolation in normal observers may be small under certain circumstances. Therefore, when the technique is used to examine pathologic states, it may be necessary to employ at least two target wavelengths to determine the cone mechanism that is performing target detection. Furthermore, we suggest that MWS cone mechanism isolation may be improved through the combination of the so-called silent substitution technique with that of selective adaptation.